TITIK TETAP NADLR FUNGSIMULTI NILAI KONTRAKTIF PADA RUANG METRIK Ï°(X) - Rinurwati, Rinurwati (MATEMATIKA, 2010)
In this paper to be discussed about Nadlr fixed point of contractive multivalued function on. This results can be considered as a generalizations of Bollobus et al result complete metrice space X.